Healthy Eating: Drink to Your Health - Jennifer Hillan; Emily Minton; Linda B. Bobroff (EDIS)
Shakes and smoothies are a great and delicious way to incorporate more fruits and nutrients into your diet. This 2-page fact sheet is a major revision which provides a variety of refreshing and exciting smoothie and shake recipes as well as preparation tips. Written by Jennifer Hillan, Emily Minton, and Linda B. Bobroff, and published by the UF Department of Family, Youth and Community Sciences. Original publication date: March 2004. Revised March 2012 and September 2015.